Maps to assemble: of booklets, manuals and guides on participatory mapping - Fenner Sánchez, Gabriela Mariana; Zaragocin, Sofía; Cubillos Alfaro, Froilán; González Ibáñez, Álvaro Ignacio; Monroy Hernández, Julieth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Taking up the contributions and reflections arising from the forum of the same name, held in October 2020, the text addresses the relevance of participatory mapping in different contexts of dispute, dispossession or territorial vindication experienced in the Latin American region, especially due to the neoliberal extractive model prevailing in their economies. We emphasize the processes followed by the five participating collectives for the elaboration of didactic materials for their implementation. This allows understanding that the guides, booklets and manuals serve firstly as tools for the systematization of experiences that play a practical, pedagogical and political mediation role in the vindication and construction of diverse, counter-hegemonic or resisting territorialities. Secondly, they become instruments for the transmission of knowledge both in the university environment, facilitating the incorporation of new generations to this critical and popular approach to cartography, as well as towards other sectors or territories in similar contexts. Finally, we evidence some of the ethical and pedagogical challenges of these materials of collective elaboration, which more than a product of diffusion, they function as devices of dialogue and reflection from and for the territorial action.